Critical Wind Direction Angles and Edge Module Vulnerability in Fixed Double-Row Photovoltaic (PV) Arrays: Analysis of Extreme Wind Conditions Based on CFD Simulation - Yuheng Hu; Hongzhou Zhang; Zhenwei Luo; Yupeng Zhou; Guoshun Yuan (Energies)
Fixed double-row photovoltaic (PV) arrays are susceptible to wind-induced damage, while their wind load characteristics remain inadequately investigated. This study employs computational fluid dynamics (CFD) simulations to systematically analyze wind load behavior under varying operational conditions, aiming to identify critical scenarios and structural vulnerabilities. First, the validity of the CFD methodology was verified through direct comparison between wind tunnel pressure measurements of an isolated PV module and corresponding numerical simulations. Subsequently, scaled PV array models were constructed to replicate practical engineering configurations, enabling a systematic evaluation of wind direction effects on mean net wind pressure coefficients and three-component force coefficients. Finally, surface wind pressure distribution patterns were examined for four representative wind angles (0°, 45°, 135°, 180°). Results demonstrate that edge-positioned modules exhibit maximum mean net wind pressure coefficients and three-component force coefficients under oblique wind angles (45° and 135°), which are identified as the most critical operational conditions. In contrast, minimal wind loads were observed at a 90° wind angle, indicating an optimal orientation for array installation. Additionally, significantly higher surface wind pressure coefficients were recorded for edge modules under oblique winds (45°/135°) compared to both interior modules and other wind angles. It was found through the study that under upwind conditions (0–90°), the lower-row components are capable of withstanding greater wind loads, whereas under downwind conditions (90–180°), an increase in the loads exerted on the upper-row components was observed.